VR Malaysia FestiWorlds: Development of 3D Virtual Reality Application - Goh, Xiu Jun; Md. Fudzee, Mohd Farhan (Applied Information Technology And Computer Science, 2024)
Malaysia is renowned for its multicultural diversity, with each ethnic group having distinct cultural traditions and celebrating various festivals. Unfortunately, the cultural gap is widened due to a decline in the transfer of traditional knowledge and festival experiences to younger generations. Thus, this research introduces VR Malaysia FestiWorlds to preserve and promote Malaysia’s multicultural festivals by providing an immersive interaction in a 3D virtual festival celebration environment. The target users for this project are public aged 7 and above. TRES-D methodology employed to develop the application by utilizing primary school sixth-grade history textbooks and subject matter experts as a guide. The implementation of VR technology allows users to virtually explore Malaysia’s multicultural festivals without being physically present, presenting an opportunity for future cultural preservation efforts and educational enhancements. The method used in user acceptance testing was based on the System Usability Scale (SUS). The Acceptability Ranges score scale places the average score of 86.25 into the "acceptable" range and "Excellent" is the adjective rating. Overall, the built-in application effectively satisfies the needs of the target users.